Social Studies Education Responding to the Challenges of the 21st Century: A Critique of Learning Practices in Elementary Education - Silvia Tabah Hati (Universitas Pahlawan Tuanku Tambusai, 2021)
21st Century Education is inseparable from technology and information. Technology and Information are the most important components and have always been the needs of the increasingly rapid era, especially in the environment of elementary school children (SD / MI). Writing this article aims to see the relevance of social studies learning in SD/MI with 21st Century skills and find out what skills are acquired through social studies learning in SD/MI. So that they are able to master the skills needed in the 21st century. This research is a conceptual (empirical) study that is library research. This was done, because the researcher used a synthetic analysis of various Sinta accredited articles and books related to social studies education in the 21st century. The results of the study illustrate that social studies learning in SD/MI is still in line with the needs and demands of the 21st century. /MI has 4 capabilities. First, social skills. Second, communication skills. Third, networking or collaboration skills. Fourth, communication skills. The 21st century itself provides demands for skills that must develop in the social studies learning process. So that in the social studies teaching process innovation is needed in various models and learning methods